Poster 117: An Activity Scale for All Youth Athletes? An Analysis of The Hss Pedi-Fabs in 2274 Pediatric Sports Medicine Patients. Issue 7 (30th July 2022) - Carpenter, Connor; Cooper, Savannah; Wilson, Philip; Miller, Shane; Wyatt, Charles; Johnson, Benjamin; Shea, Kevin; Ellis, Henry
Objectives: The HSS Pedi-FABS activity scale has become increasingly used in children age 10-18 since its development in 2013. Research reports on the utility of the measure in general youth athletes with knee injuries, however limited information is available regarding use in evaluating a variety of joint injuries, athletes who participate in sports with disparate biomechanics, or specialized competitive athletes. This study assessed the sensitivity and distribution of Pedi-FABS in an athletic youth population. Secondarily, this study evaluated Pedi-FABS association with PROMIS® Pediatric Global Health 7(PGH7) with Pain Interference(PGHPI) and Fatigue(PGHF) components. Methods: A retrospective review of youth athletes age 10-18 presenting for evaluation at a single pediatric sports medicine clinic between 4/2016-7/2020 was performed. Participants were included if they completed a pre-visit intake questionnaire and Pedi-FABS. Descriptive statistics were used to analyze Pedi-FABS for normal distribution and the presence of a floor or ceiling effect in subgroups determined by demographics, injury characteristics, and sports participation. A floor or ceiling effect was determined to be present if more than 15% of respondents scored the lowest or highest possible score. A Kruskal-Wallis test used to compare average scores in each subgroup. Spearman's Correlations were calculated to assess the association of PGH with Pedi-FABS scores. Results: 2274 sports medicine patients (14.6±2.1 years; 53.0% females) were included. Of these, 2010 youth athletes reported participating in sports for 9.6±7.9 hours per week during 32.3±15.7 weeks per year with 6.2±3.4 years of participation in 21 distinct primary sports. 80.3% of patients reported participation in only one sport. Pedi-FABS Score differences were found across demographic(Table 1) and sport participation(Table 2) subgroups. Broad distribution was seen in each subgroup with no floor or ceiling effects. Pedi-FABS score correlated with hours per week(r=0.20), days per week(r=0.28), weeks per year(r=0.12), and years of participation(r=0.16/p<0.01). An inverse correlation was observed between Pedi-FABS and Days from Injury to Presentation(r=-0.21/p<0.01). An association between general health and activity level was noted as all three PGH components correlated with Pedi-FABS(PGH7: r=0.28/PGHF: r=-0.16/PGHPI: r=-0.12, p<0.01). Conclusions: Correlations with multiple forms of self-reported activity without floor or ceiling effects demonstrates the validity and sensitivity of Pedi-FABS for use in athletes with a variety of primary sports and injury types. Additionally, mean differences between demographic and sport participation subgroups, as well as associations with days to presentation and a commonly used patient reported outcome measure, may demonstrate the utility of Pedi-FABS for sports medicine clinicians. Table 1. HSS Pedi-FABS Score Distributions by Study Cohort Demographics and Injury Characteristics Table 2. HSS Pedi-FABS Score Distributions by Sports Participation Characteristics Among Self-Reported Athletes in Study Cohort